Mineral mixture supplementation for enhancing milk yield of milch animals in Haryana - R R BURMAN; GOUTAM MONDAL; J P SHARMA; SHAILENDRA SHARMA; RAJESH KUMAR; RAHUL SINGH; V P CHAHAL; A K SINGH (Indian Journal of Animal Sciences, 2020)
Most of the Indian soils are deficient in one or more minerals and these minerals are important in numerous biochemical reactions and deficiency may lead to metabolic diseases resulting lowering production performance in dairy animals. The study attempts to evaluate status nutrient intake in dairy animals, effect of reappropriation of available feed resources and mineral mixture supplementation on production performance in lactating cows and buffaloes in Katesara and Amarpur villages under Farmers’ FIRST project in Palwal district. The animals were in their early lactation (40±5 days in milk) and milk yield, its composition, body weight and body condition score was recorded. Among the cow, 28% deficit, 35% excess dry matter; 41% deficit and 11% excess crude protein; 33% deficit and 25% excess total digestible nutrients (TDN) was provided. In buffaloes, 36% deficit and 40% excess DM; 45% deficit and 15% excess CP; 25% deficit and 12% excess TDN was provided. Reappropriation of DM, CP and TDN was done using available feed/ fodders available to the farmers and after 15 days, mineral mixture was provided @ 50 g/d for 60 days. The production performance record reveals no change in body weight but BCS was improved. Milk yield, fat, protein in cows were improved and other composition were remain unchanged. In buffaloes, milk yield, fat and protein improved while others, viz. lactose, SNF, ash and TS were similar due to supplementation of mineral mixture. The results conclude that imbalance of nutrients existed to the tune of 10 to 45% among various nutrients. One of the best propositions could be supplementation of mineral mixture to improve milk yield (10 to 14%) and fat per cent under field condition in both cows and buffaloes.